1999
DOI: 10.1103/physreve.60.4908
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of dislocated wave fronts by vertical vorticity and the Aharonov-Bohm effect. I. Shallow water

Abstract: When a surface wave interacts with a vertical vortex in shallow water the latter induces a dislocation in the incident wave fronts that is analogous to what happens in the Aharonov-Bohm effect for the scattering of electrons by a confined magnetic field. In addition to this global similarity between these two physical systems there is scattering. This paper reports a detailed calculation of this scattering, which is quantitatively different from the electronic case in that a surface wave penetrates the inside … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 23 publications
1
51
1
Order By: Relevance
“…2 for different values of these background parameters. For each curve, the location of the event horizon, found using (45), is indicated by an asterisk. Note thathðrÞ is always a strictly increasing function ofr, so that the slope of the water surfaceh 0 ðrÞ is always a decreasing function.…”
Section: B Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 for different values of these background parameters. For each curve, the location of the event horizon, found using (45), is indicated by an asterisk. Note thathðrÞ is always a strictly increasing function ofr, so that the slope of the water surfaceh 0 ðrÞ is always a decreasing function.…”
Section: B Results and Discussionmentioning
confidence: 99%
“…By using a combination of theory and numerical simulations, we have calculated the reflection coefficients for incident waves and have shown that there exists a window of physical parameter space where our approximations are satisfied and superradiant amplification is predicted. It is important to note that this effect is different from the hydrodynamic analogue of the Aharonov-Bohm effect, which is characterized by dislocation and discontinuity in the incident wavefronts [44][45][46][47].…”
Section: Final Remarksmentioning
confidence: 99%
“…16,17,18 for the acoustical AB effect, Refs. 19,20,21,22 for the hydrodynamical AB effect and Ref. 23 for the optical AB effect).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning other works that have investigated the Aharonov-Bohm effect [55][56][57][58][59][60][61][62][63][64][65]. In this way, the Klein-Gordon equation (18) becomes:…”
Section: Aharonov-bohm Effect For Bound Statesmentioning
confidence: 99%